A surprising finding during solid‐phase gastric emptying scintigraphy - Anne‐Sophie Hambye (Wiley, 2021)
Abstract In case of repeated episodes of abdominal discomfort and vagal symptoms, especially occurring after ingestion of a rich meal, the diagnosis of intermittent volvulus could be considered. The sudden arrival of large amounts of partially digested food in the intestine after spontaneous resolution might be associated with a dumping syndrome.